Why a future commercial spacecraft must be able to SWIM. Issue 1 (March 2017) - Morlang, Frank; Ferrand, Jorge; Seker, Remzi
Abstract: Regarding current as well as future commercial space transportation (CST) projects, new re-entry trajectory profiles, differing from capsule and shuttle-like approaches, have to be taken into account. These characteristics are mainly ruled by the principle of "landing like an aircraft at an airport". This directly generates the need to be taken in a system wide information management (SWIM) consideration because of the fact, that all the future air traffic participants are requested to act as SWIM communicating sub-systems by the future Single European Sky Air Traffic Management Research (SESAR) SWIM "Intranet for ATM" concept. Against the background of the global character of future CST operations and the associated SWIM harmonization need referring the U.S. Next Generation Air Transportation System (NextGen) and SESAR, the presented solution addresses near real-time information sharing for normal air traffic protection purposes in the event of a future space vehicle breakup and bases on the already harmonized data format standards Aeronautical Information Exchange Model (AIXM) and Flight Information Exchange Model (FIXM).